PERBEDAAN KOMPRES AIR HANGAT DAN JAHE MERAH TERHADAP TINGKAT NYERI GOUT LANSIA - Merliana, Rita; Daeli, Novita Elisabeth; Sitanggang, Morlina (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Increased uric acid levels in the blood (hyperuricemia)is cause by buildup of uric acid levels and its know as a gout illness. Decreasing of kidney function such as disability, inflammation, swelling, redness and pain that disrupts daily activities are some of the effects caused by gout. Gout pain can be handledby pharmacological and non-pharmacological therapy. The example of Non-pharmacological therapy like warm water compress therapy and red onion compress (zingiber officinale var rubrum).To determine the differences of warm water compresses and red onion compress (zingiber officinale var rubrum) of gout pain level in the elderly at the Palembang Nursing Home. This study used a quantitative study, with a quasi-experimental design method by pretest posttest design, sampling used a total sampling of 42 respondents. Bivariate analysis using the Wilcoxon and Mann-Whitney tests.The characteristic of all respondents are aged 60-74 years (100%), the majority of female sex (66.7%), uric acid levels> 7.1 mg / dL (61.9%), the level of pain pretest (7- 9) (59.5%), posttest (1-3) (66.7%), type of gout therapy: warm water compress (50%), red onion compress (50%). Wilcoxon test results show that warm water compresses with p value: 0.00 and red onion compresses with p value: 0.00, its mean that there are differences before and after the intervention given to the extent of gout pain. Mann-Whitney test with p value 0.518 indicates that there is no difference in warm water compresses and red onion compress with mean rank of red onion compress is 20.50 and mean rank of warm water compresses is 22.50.Warm water compress and red onion compress together can reduce pain but red onion compress are more effective. This research is expected to be a reference for using red onion compress (zingiber officinale var rubrum) as a one non-pharmacological therapy to treat gout pain in the elderly.Keywords: Gout, gout pain, warm water compress, red onion compress